Pertumbuhan Penduduk dan Tantangan Pembangunan Lingkungan di Kelurahan Pipitan, Kota Serang - Aisyah Shofiyati; Akrom (PT. Saha Kreasi Indonesia, 2026)
This study analyzes the relationship between population growth and environmental development challenges in Pipitan Village, Serang City. Data from the Central Bureau of Statistics of Serang City in 2023 shows that the population reached 12,750 people, an increase of 18 percent from 2015. This surge has triggered massive land conversion, a reduction in Green Open Space from 21 hectares to only 11.2 hectares, and an increase in waste volume from 3.2 tons to 5.6 tons per day. The research method uses a descriptive qualitative approach with in-depth interviews with two key informants, Supenah and Safitri, as well as field observations. The results show that population growth has led to a clean water crisis, local flooding in 14 locations, declining air quality due to a surge in motor vehicles from 1,800 to 3,450 units, and a gap between reactive government policies and community participation. The existence of the Pipitan Tourism Village has proven to increase residents' environmental awareness. This study recommends spatial planning based on environmental carrying capacity and improved collaboration between the government and the community.